2008
DOI: 10.2174/1874282300802010166
|View full text |Cite
|
Sign up to set email alerts
|

Emission Scenario Assessment of Gasohol Reformulation Proposals and Ethanol Use in the Metropolitan Area of São Paulo

Abstract: Abstract:The frequent episodes of high concentrations of ozone and of inhalable particulate matter occurring in the Metropolitan Area of Sao Paulo (MASP) are primarily associated with vehicle emissions. The objective of this study was to evaluate the impact of the use of reformulations of the gasoline-ethanol blend known as gasohol and of ethanol on the ozone formation. A three-dimensional photochemical model was employed to estimate the sensitivity of ozone and evaluate the implementation of emission scenario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…In two studies employing that model Vivanco and Andrade, 2006), the atmosphere of the MASP was found to have a high potential to form ozone and that the concentrations of nitrogen oxides (NO x ) in the official emissions inventory are twice as high as those that would be expected on the basis of modeling results and the concentrations measured at air quality monitoring stations. Important aspects of ozone formation in the MASP were studied by Martins et al (2006), who identified the main precursors of tropospheric ozone, and by Martins and Andrade (2008a), who demonstrated an increase in the reactivity of the ozone precursors in the region.…”
Section: Wwwfrontiersinorgmentioning
confidence: 99%
“…In two studies employing that model Vivanco and Andrade, 2006), the atmosphere of the MASP was found to have a high potential to form ozone and that the concentrations of nitrogen oxides (NO x ) in the official emissions inventory are twice as high as those that would be expected on the basis of modeling results and the concentrations measured at air quality monitoring stations. Important aspects of ozone formation in the MASP were studied by Martins et al (2006), who identified the main precursors of tropospheric ozone, and by Martins and Andrade (2008a), who demonstrated an increase in the reactivity of the ozone precursors in the region.…”
Section: Wwwfrontiersinorgmentioning
confidence: 99%
“…It is considered that the chemical regime remains VOC-limited (Martins and Andrade, 2008a;Sánchez-Ccoyllo et al, 2006). Recent studies suggested that O3 concentrations can be reduced in MASP by shifting from ethanol to gasohol by flex-fuel cars (Martins and Andrade, 2008b), which has in fact been promoted by an increase of ethanol price in 2010 (Salvo and Geiger, 2014).…”
Section: Main Textmentioning
confidence: 99%
“…Simulation and optimization are also used, primarily to assess the potential impacts of a policy change. Notable examples include the effect of urban form on energy use for water systems [225], predicting greenhouse-gas emissions for a Japanese city [226,227], and the impact of transportation system changes [228][229][230][231][232].…”
Section: Case Studies Of What Work and What Doesn't In Urban Energymentioning
confidence: 99%